HPV16 E7 oncogene expression in normal human epithelial cells causes molecular changes indicative of an epithelial to mesenchymal transition. - Hellner, K; Mar, J; Fang, F; Quackenbush, J; Münger, K (2009)
Cancer-associated epithelial to mesenchymal transition (EMT) is crucial for invasion and metastasis. Molecular hallmarks of EMT include down-regulation of the epithelial adhesion protein E-cadherin and de-novo expression of N-cadherin and the mesenchymal intermediate filament proteins vimentin and fibronectin. Expression of HPV16 E7 in normal human epithelial cells caused increased levels of vimentin and fibronectin, whereas the epithelial adhesion protein E-cadherin was expressed at decreased levels. Similar expression patterns of vimentin, fibronectin and E-cadherin were also detected in cells expressing HPV16 E6 and E7 or the entire HPV16 early transcriptional unit. HPV16 E6 and E7 were each able to induce N-cadherin expression. Interestingly, these changes in expression levels of EMT-associated proteins are not similarly reflected at the level of mRNA expression, suggesting that HPV16 oncoproteins also modulate EMT through non-transcriptional mechanisms. Hence, HPV16 oncoproteins may contribute to malignant progression through EMT induction.